Conflict in Practice-based Settings: Nature, Resolution and Education - Thistlethwaite, Jill E.; Jackson, Ann (International Journal of Practice-based Learning in Health and Social Care, 2016)
In this masterclass we review the evidence regarding the nature of conflict within healthcare practice settings, discuss ways of preventing and resolving conflict, and consider how practice-based education, focusing on conflict and negotiation, may help learners achieve positive outcomes. Conflict is a serious state, which is often prolonged and arises from incompatibility or divergent interests and values. However, conflict may also be used as a productive force for change. Conflict has been included as a core competence for healthcare professionals in a number of competency frameworks because of the recognition that inter- and intra-professional conflict affect patient safety and outcomes, as well as having detrimental effects on staff morale, and on physical and mental health. We discuss how conflict may arise from several triggers – personal, professional and organisational. In particular, disparities in values may lead to conflict, while good communication is fundamental to optimal practice. The history of the development of the health professions includes many examples of conflict between professional groups. A healthy practice environment should encourage constructive conflict management, recognising that conflict will always arise. Early experiences of working and learning together represent important learning opportunities for students, enabling the development and practice of teamwork skills, as well as helping them to recognise and understand the different values, perspectives, roles and responsibilities of team members. Learning opportunities based on real-life scenarios and patient experiences provide a focus common to all professional groups, allowing students the opportunity to explore their differences and similarities. The key messages are: conflict occurs frequently in practice-based settings both inter- and intra-professionally, and learners need to be able to recognise and deal with conflict, including through negotiation.